Der Schutzauftrag des Rechts : Referate und Diskussionen auf der Tagung der Vereinigung der Deutschen Staatsrechtslehrer in Berlin vom 29. September bis 2. Oktober 2010. (De Gruyter, 2011)
This volume contains essays and discussions from the conference of the Association of German Constitutional Law Instructors held September, 29 - October 2, 2010 inBerlin.
Keywords: Law -- Germany -- Congresses.; LAW -- Constitutional.; LAW -- Public.; Law.; Germany.; Law - Non-U.S.; Law, Politics & Government.; Law - Europe, except U.K.; Electronic books.; Conference papers and proceedings.